Modern Innovative Education Process and Its Structural Analysis Challenges (Eurasian Scientific Herald, 2023)
The presented article deals with the issues stating, that educating intellectually advanced generation is the ultimate goal of Uzbekistan for the construction of the great state. Education structural system is a whole science today. It is in the constant process of change according to the laws of development, but first of all its structure is a part of science.